2020
DOI: 10.1002/qj.3904
|View full text |Cite
|
Sign up to set email alerts
|

Lagrangian trajectories at the outflow of tropical cyclones

Abstract: Recent observations from the upper levels of tropical cyclones show the development of a Low engulfed by a larger High. The impact of such a geopotential map on the dynamics of the outflow is studied by analysing the Lagrangian trajectories of air parcels. The geopotential is modelled by the hydrostatic sum of two, oppositely signed, Gaussians: a warm core and a near‐surface low that together reproduce the relevant features of the observed tropical cyclones. Assuming a time‐independent and axisymmetric geopote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…For a field of air parcels moving in a prescribed pressure field, the mass continuity constraint must, in general, be forfeited. On these grounds, we have reservations about the results of the Cohen and Paldor study.…”
Section: Relationship To Other Studiesmentioning
confidence: 95%
See 1 more Smart Citation
“…For a field of air parcels moving in a prescribed pressure field, the mass continuity constraint must, in general, be forfeited. On these grounds, we have reservations about the results of the Cohen and Paldor study.…”
Section: Relationship To Other Studiesmentioning
confidence: 95%
“…A more recent article is that by Cohen and Paldor (2020). Whereas our trajectory calculations are based on a three‐dimensional numerical simulation and focus on trajectories that start within the inflow layer below the outflow layer, Cohen and Paldor consider only trajectories in the outflow layer within an axisymmetric configuration. Moreover, they prescribe the pressure gradient in this layer.…”
Section: Relationship To Other Studiesmentioning
confidence: 99%
“…Both model simulations (Cohen et al, 2017) and observations (Cohen et al, 2019) suggested that the outflow layer may exhibit a lowpressure center surrounded by high pressure due to the strong outward-pointing centrifugal and pressure gradient forces that cannot be counterbalanced by the inward-pointing Coriolis force. Furthermore, Cohen and Paldor (2020) analyzed the Lagrangian trajectories of air parcels in the outflow layer and described the dynamics using an integrable, two degrees-offreedom and angular momentum conserving Hamiltonian system with a single non-dimensional parameter. Several studies focused on the characteristics of low Richardson number in the outflow layer (Emanuel and Rotunno, 2011;Emanuel, 2012;Duran and Molinari, 2016).…”
Section: Introductionmentioning
confidence: 99%